1989
DOI: 10.1016/0361-3682(89)90025-1
|View full text |Cite
|
Sign up to set email alerts
|

The use of accounting information in bank lending decisions

Abstract: This paper examines the impact of accounting information on the sequential judgments of experienced bank loan officers using realistic lending cases in an experimental setting. The findings suggest that loan officers reach a high level of confidence early in the lending process based on summarized accounting information and other general background data. When, later in the process, factors concerning the firm's financial plans and their underlying assumptions are varied, lenders adjust their confidence in whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 6 publications
2
53
0
4
Order By: Relevance
“…Loan officers are under pressure to generate loan volume to meet bank profit goals (McNamara and Bromiley, 1997). They reach a high level of confidence early in the lending process based on summarized accounting and other general background data (Danos et al, 1989).…”
Section: Previous Research On Funding Decision Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Loan officers are under pressure to generate loan volume to meet bank profit goals (McNamara and Bromiley, 1997). They reach a high level of confidence early in the lending process based on summarized accounting and other general background data (Danos et al, 1989).…”
Section: Previous Research On Funding Decision Criteriamentioning
confidence: 99%
“…The photo in Fay and Williams's (1993) experiment may well have affected the loan decision rather than the proposal itself. Danos et al (1989) looked at the impact of accounting information on the judgement using cases, where variables were manipulated.…”
Section: Critique Of Previous Research and Rationale For This Researchmentioning
confidence: 99%
“…Examining the bank lending process, Danos et al (1989) have showed how the loan officers can use various types of accounting information in banks' credit-granting decision process: at the first stage the bank examines publicly available data on potential borrower in order to make a preliminary judgment on the quality of the proposed loan. So, the loan officers try to gather background information on firm's history and financial report information.…”
Section: Literature Review On the Bank Lending Processmentioning
confidence: 99%
“…firm rating) which supported the managers in the decisions related to grant or not grant the proposed loan. The lending decision has to take into account many attributes that cannot always be weighted in a normative way (Danos, Holt, & Imhof, 1989;Crouhy, Galai, & Mark, 2001). Thus, sharing (quantitative and qualitative) information represents a very important point in order to create a sufficient knowledge which could help to manage the risk in the bank-business relationships (Neef, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This study continues to learn more about financial reporting's quality issues to make specific recommendations which help enhance their usefulness for business borrowing activities. (Danos, Holt, & Imhoff, 1989). Operating cash flow was demonstrated to have a close relationship with credit risk at enterprises which have high long-term loan rates or less business risks (Independent Evaluation Group [IEG], 2010).…”
Section: Introductionmentioning
confidence: 99%